Adaptation of infectious bursal disease virus in chicken embryo fibroblast cell culture and its fine structure - KUMAR, RAJESH; CHANDRA, R; RAO, V D P; SHUKLA, S K (The Indian Journal of Animal Sciences, 2013)
Two outbreaks of suspected infectious bursal disease (IBD) at university poultry farms were investigated. On the basis ofepidemiological data, characteristic gross and microscopic changes in different organs including bursa of Fabricius (BF)and spleen, presence ofIBD virus antigen in BF and demonstration of intracytoplasmic virus particles of 59.2 nm diameter in infected chicken embryo fibroblast cells by transmission electron microscopy confirmed the outbreak as IBD. The type and distribution of lesions and mortality up to 23.2% is highly suggestive of involvement of IBD virus of moderate virulence. Neutralization of cell culture grown virus with reference antisera revealed the identity of virus as IBDVserotype 1.